Passive Direct Air Capture of Carbon Dioxide with an Alkaline Amino Acid Salt in Water-Based Paints - Godwin Ngwu; Humbul Suleman; Faizan Ahmad; Danial Qadir; Zufishan Shamair; Qazi Nasir; Muhammad Nawaz (Energies, 2024)
The current study presents the first results of the passive capture of carbon dioxide from the air in aqueous sodium lysinate solutions at ambient conditions. The salt has shown good passive direct air capture (DAC) properties for carbon dioxide with spent solutions exhibiting more than 5% carbon dioxide by weight. Moreover, different quantities of sodium lysinate solutions were mixed with three commercial water-based paints, and their passive DAC performance was studied for 45 days. An average improvement of 70% in passive DAC capacity compared to the control sample was observed across all the studied paint samples. The results establish that a litre of water-based paint doped with sodium lysinate can absorb up to 40 g of CO2 and fix it stably for a short period of time, i.e., 45 days. Such paints can be used to directly capture carbon dioxide from the air. However, further research is required to address various technicalities and establish long-term sequestration.